2021
DOI: 10.1108/jgoss-01-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

Managing supplier capabilities for buyer innovation performancein e-business

Abstract: Purpose The purpose of this paper is to analyze the connections between the capabilities of suppliers, buyer operations and the innovation performance of buyers in service-based supply chains. In particular, the authors use a construct of supplier capabilities comprising the capabilities needed to produce an online store and divided into capabilities related to the product, capabilities related to service delivery and capabilities related to the buyer-supplier relationship. Design/methodology/approach Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
(118 reference statements)
0
6
0
Order By: Relevance
“…The production process includes different activities such as manufacturing, services, maintenance, operational repairs and product design. Moreover, building a local production network is necessary for long-term development and supports innovation, as evidenced by previous studies (Kumar et al , 2015; Saunila et al , 2021; Wang and Lee, 2007; Xiao and Shi, 2016). Organizations, as a part of their inventory management strategy, ensures a maximum level of collaboration with suppliers and utilization of all available facilities, minimizing stock level, reduction in transportation cost, and finally, using the sources (Che Omar et al , 2020; Guo et al , 2016; Thompson et al , 2020).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 76%
See 1 more Smart Citation
“…The production process includes different activities such as manufacturing, services, maintenance, operational repairs and product design. Moreover, building a local production network is necessary for long-term development and supports innovation, as evidenced by previous studies (Kumar et al , 2015; Saunila et al , 2021; Wang and Lee, 2007; Xiao and Shi, 2016). Organizations, as a part of their inventory management strategy, ensures a maximum level of collaboration with suppliers and utilization of all available facilities, minimizing stock level, reduction in transportation cost, and finally, using the sources (Che Omar et al , 2020; Guo et al , 2016; Thompson et al , 2020).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 76%
“…The production process includes different activities such as manufacturing, services, maintenance, operational repairs and product design. Moreover, building a local production network is necessary for long-term development and supports innovation, as evidenced by previous studies (Kumar et al, 2015;Saunila et al, 2021;Wang and Lee, 2007;Xiao and Shi, 2016).…”
Section: Supply Chain Inventory and Small And Medium Enterprises Perf...mentioning
confidence: 86%
“…Accordingly, wide extents of literatures are evaluated in present study under the domain of supplier selection to understand crucial aspects in construction projects works. Supplier selection and evaluation decisions are significant in SCM (Saunila et al , 2021) and own multiple aspects, which are needed to be identified and appraised for accounting effectual profits, saving in revenues and executing hassle free work (Sahu et al , 2016). Suppliers play a significant role in the success of SC (Yadav and Barve, 2018; Faisal et al , 2017).…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Supplier evaluation is a complex process and their appropriate selection is paramount for successfully completing any construction project under predefined time, cost, quality and safety (Weber, 1991; Saunila et al , 2021). It is instigated that the supplier source selection measures can entail efficacy in whole SC deeds and that too are needed to rethink in post COVID-19 pandemic to authenticate the success of organization goals.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…The same may lead in attaining transformation toward global SC. The transformation can provide reinforce capabilities to the firms, aid in maintaining inventories and assist in ease applying proactive strategies of shifting manufacturing assets and services under broader domain (Saunila et al , 2021; Hariyani and Mishra, 2022). Agile criteria can develop capabilities related to suppliers, store management, workforce handling, product variants, service delivery and capabilities related to the buyer–supplier relationship.…”
Section: Introductionmentioning
confidence: 99%